2010
DOI: 10.2174/138920310790848386
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Prion Protein and Its Gene: An Analysis Using Bioinformatics and Computer Simulation

Abstract: Prion protein (PrP) gene encodes cellular PrP (PrPC), a glycosylphosphatidylinositol (GPI)-anchored cell membrane protein indispensable for infections of prion, which causes Creutzfeldt-Jakob disease (CJD) in humans, bovine spongiform encephalopathy (BSE) in cattle, and scrapie in sheep. Although PrPC is known to be converted into an abnormal isoform (PrPSc) upon prion infection and play an important role in prion diseases, the mechanisms involved remain unclear, partly due to the insolubility of PrPSc, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…Candidate transcription activators that may bind to binding sites identified in exon 1 include Sp1, AP-2, and C/EBPα. The expression of many genes is regulated by elements within exon 1 [19], [20], one report shows that exon 1 may also be involved in PRNP regulation [15]. Proteins binding within the exon 1 region repress transcription of the PRNP promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate transcription activators that may bind to binding sites identified in exon 1 include Sp1, AP-2, and C/EBPα. The expression of many genes is regulated by elements within exon 1 [19], [20], one report shows that exon 1 may also be involved in PRNP regulation [15]. Proteins binding within the exon 1 region repress transcription of the PRNP promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Although PRNP has a short GC-rich region immediately upstream of its transcription start site, as well as other features common to housekeeping genes (Puckett et al, 1991; Sakudo et al, 2010), intron 1 and the sequences upstream of the transcription start site also contain evolutionarily conserved, putative binding sites for numerous transcription factors, including Sp1 (Basler et al, 1986), activator proteins 1 and 2 (Mahal et al, 2001), forkhead box protein O3 (Liu et al, 2013), regulatory factor X1, heat shock factor 2, GATA-binding factor 3, thyrotrophic embryonic factor, myocyte enhancer factor 2, ecotropic viral integration site 1, E4 promoter-binding protein, 4 and nuclear matrix protein 4/cas-interacting zinc finger protein (Kim et al, 2008). These regulatory sequences presumably enable dynamic control of PrP C expression in response to various stimuli, for example, treatment of cultured cells with nerve growth factor, insulin or insulin-like growth factor induces PrP C expression (Kuwahara et al, 2000; Zawlik et al, 2006; Liu et al, 2013).…”
Section: The Cellular Prion Protein and Its Genementioning
confidence: 99%
“…5 Prion protein (PrP) is encoded by the PrP gene ( PRNP ) and is strongly conserved among mammals. 6 PrP C is a protein of 210 amino acids in length that resides mainly on the surface of the mammalian neuronal cells through C-terminal glycosylphosphatidyl inositol anchors, although it is also expressed in other cell types. 7 Nuclear magnetic resonance spectroscopy has indicated that the C-terminal region of PrP C forms a highly structured globular domain and the N-terminal region forms a non-structured flexible tail.…”
Section: Introductionmentioning
confidence: 99%
“…9 Sequence variation in the PrP gene appears to be important, as it changes the susceptibility to prion disease. 6, 10 Moreover, the M129V polymorphism of human PrP affects resistance to sporadic CJD. 11 The E219K polymorphism is not found in sCJD patients, suggesting resistance to sCJD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation